Success of farmer FIRST Project in enhancing income of mango farmers of Malihabad, Uttar Pradesh - Mishra, Maneesh; Verma, Anil Kumar; Shukla, P K; Shukla, S K; Ram, R A; Jaiswal, Rohit; Singh, Pravesh Kumar; Dubey, Shantanu Kumar; Ravi, S C (Indian Farming, 2022)
It is evident from the experience gained from Farmer FIRST project that right information to farmers at right time on right aspect and right motivation helps the fast spread of technologies and also helps the farmers to increase their income sustainably. Mango GAP, mango orchard-based poultry farming, intercropping in mango orchards have an immense potential in enhancing the income of the farmers and these technologies should be made available to the large number of farmers in various others parts of the state as well as country. Entrepreneurship development activities such as mushroom farming, value-addition and nursery are very viable enterprises which help in increasing the employment and income of farm women as well as rural youth.